Pengaruh Sanksi Perpajakan dan Sistem Samsat Drive Thru terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Irvandi, Irvandi; Praditha, Riza (Tangible Journal, 2023)
This study aims to determine the effect of tax sanctions and the drive thru samsat system on motor vehicle taxpayer compliance. The data uses quantitative data sourced from primary data in the form of a questionnaire. The population used in this study are two-wheeled motorized vehicle taxpayers who are registered on the SAMSAT drive thru. Through the incidental sampling method, 115 taxpayers were sampled in this study. The results of this study indicate that tax sanctions and the drive thru samsat system have a positive and significant effect on motor vehicle taxpayer compliance.